Understanding Sacred Food Behaviours: A Salutogenic Framework for Waste Reduction - Aryastami, Ni Ketut; Notobroto, Hari Basuki; Kurnianingsih, I Desak Ketut Dewi Satiawati (Universitas Airlangga, 2026)
Background: Sacred food waste lies at the intersection of cultural practice, environmental sustainability, and public health. Single-theory approaches have been insufficient to explain this complexity, limiting the development of effective health promotion strategies. This paper addresses this gap by adopting a salutogenic perspective that emphasizes the resources and pathways that promote well-being. Objective: To develop a novel, integrated conceptual framework—grounded in the salutogenic model—that explains sacred food waste across multiple levels. By integrating the Theory of Planned Behaviour (TPB), Social Practice Theory (SPT), and Habitus, the framework provides a foundation for designing health-promoting interventions. Methods: An integrative literature synthesis framed within a salutogenic orientation was conducted. More than 60 studies were systematically reviewed to construct a multi-level framework and generate eight propositions explaining how to foster sustainable sacred food practices by enhancing Sense of Coherence (SOC) and leveraging institutional support as a Generalized Resistance Resource (GRR). Results: The framework illustrates how individual intentions (TPB), collective routines (SPT), and embodied dispositions (Habitus) interact. It argues that interventions should be salutogenic by design, enhancing comprehensibility, manageability, and meaningfulness while aligning with spiritual values. Institutional support emerges as a critical GRR capable of reconfiguring practices and cultivating a sustainable environmental habitus. Conclusion: This integrated framework shifts the focus from merely “preventing waste” to promoting sustainable, health-enhancing practices. It provides an actionable guide for multi-level interventions that reduce waste while strengthening community health, food security, and spiritual well-being.